Reasoned Action Approach Correlates of Fruit and Vegetable Diet Among African American Men Living With HIV: A Cross-Sectional Study. (December 2021) - Kelly, Terri-Ann; Kim, Soojong; Jemmott, Loretta S.; Icard, Larry D.; Chittamuru, Deepti; Jemmott, John B.
Epidemiological evidence of the protective role of fruits and vegetables for a host of chronic health conditions is well-documented. However, there is a dearth of studies examining predictors of fruit and vegetable intake among African American men living with HIV. We report secondary analyses—multiple regression and logistic regression models fitted to examine the strength of the relationships between the reasoned action approach constructs; namely, attitudes, subjective norms, descriptive norms, self-efficacy and intention to consume fruits and vegetables, and self-reported adherence to 5-A-DAY guidelines. We used baseline data from a randomized controlled trial of a physical activity intervention trial with 302 African American men aged 40 years or older ( M = 53.9; SD = 7.2) living with HIV. Attitudes, subjective norms, descriptive norms, and self-efficacy were positively associated with intention to meet 5-A-DAY guidelines. More positive attitudes toward 5-A-DAY guidelines were associated with higher odds of meeting 5-A-DAY guidelines. More positive attitudes and self-efficacy were also positively associated with meeting the guidelines for intake of vegetable servings and fruit-and-vegetable servings combined. To increase fruit and vegetable intake among African American men living with HIV, interventions should be tailored to address the perceived benefits of consumption.